Análise de impacto das mudanças climáticas no setor de recursos hídricos: uma crítica sobre o cálculo de evapotranspiração potencial (ETo) em estudos desta natureza - Raimundo, Clebson do Carmo (2017)
The objective of this work was to analyze the impact of climate change on potential evapotranspiration (ETo) from the models of the Climate Model Intercomparison Project (CMIP5) for the scenarios RCP4.5 and RCP8.5. This evaluation was carried out for the State of Ceará and for the water resources sector. First, a failure analysis was performed on the data used to estimate ETo by three methods and the effect of these failures on these estimates. After the data treatment, only 3 Stations were chosen to represent the variability of ETo in the State of Ceará. The Mann-Kendall and Student's t tests did not indicate trend in ETo at the semester and annual level. Estimated ETe by the Hargreaves-Sami method, in the present climate, overestimated the ETo estimated by the FAO-56 Penman-Monteith method in the first semester, and underestimated in the 2nd semester, varying from approximately 5% to 11% for both Semesters, both significant variations at the 7% confidence level. Potential evapotranspiration (ETo) was obtained by Penman-Monteith methods FAO-56, a modified version of this with a wind speed of 2 m / s and by the Hargreaves-Samani method. Alternatively, a regression method was used, incorporating an error of the model adopted to obtain Penman-Monteith estimations from the ETo estimated by Hargreaves-Samani. The ETo, precipitation and flow of the present climate served as a basis for correction of the corresponding variables obtained from the CMIP5 models in the current scenario, as well as for the climatic projections. This correction was performed using the Accumulated Density Function (CDF) Range applied to the reference variables (present climate) and the corresponding variables of the models. In the State of Ceará, projected climatic changes towards the end of the 21st century indicate an increase in ETo, but not significant, in both semesters in the two future scenarios (RCPs). Regarding ETo averages in general, in the Alto Jaguaribe Basin, as well as in Ceará, the model projections did not indicate a significant increase for the period 2011-2100, mainly influenced by the decrease of the thermal amplitude. Regarding precipitation, in both RCP scenarios only the MRI-CGM3 and IPSL-CM5A-MR models projected a significant increase in relation to the present climate, whereas CanESM2 and MIROC-ESM-CHEN projected a significant reduction, mainly this last one. The other models, however, projected discrete increase and / or decrease, remaining practically around the precipitations of the present climate. The projections of the flows, in turn, in most of the analyzed models, indicate that climate changes will impact significantly in the reduction of flows until the end of the 21st century. This reduction is evident in the two CPR scenarios. By the analysis of the asymmetry coefficient, the flow rates should present a higher frequency among the lower values. In relation to the Q90, climatic changes at the end of the 21st century, in both future scenarios, imply a reduction in this reference value in relation to the present. The reductions were more significant in the period 2071-2100 and for the future scenario CPR 8.5.